Sarcopenic dysphagia following COVID-19 infection: A new danger - TUFAN ÇİNÇİN, ASLI; CİNEL, İSMAİL HAKKI; ENVER, NECATİ (WILEY, 2021)
Oropharyngeal dysphagia is one of the complications of endotracheal intubation. As expected, cases of dysphagia following coronavirus disease 2019 (COVID-19) reported to date have all been intubated. We here report a case of sarcopenic dysphagia following severe COVID-19 pneumonia in a nonintubated older adult. The patient was an 85-year-old male who was readmitted to the hospital with dysphagia and subsequent aspiration pneumonia in the first week after his discharge from the COVID-19 unit. On physical examination, the patient was sarcopenic and malnourished. Flexible endoscopic evaluation of swallowing (FEES) revealed aspiration into the airway. Enteral feeding was initiated and the infusion rate gradually increased to achieve the desired protein-energy targets. Control FEES 2 months after discharge showed recovery of swallowing function, with no apparent penetration or aspiration. Clinicians caring for patients with COVID-19 should be aware that dysphagia, which is associated with increased mortality in older adults, may occur even in the absence of intubation. We recommend that the evaluation of dysphagia be part of the clinical assessment in older COVID-19 patients with malnutrition or sarcopenia.
Keywords: aspiration pneumonia; COVID-19; dysphagia; sarcopenia